2021
DOI: 10.1177/14680874211032382
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the system behavior of a two-stage variable compression ratio (VCR) system in fired SI-engine operation

Abstract: Especially for turbocharged SI engines, systems that allow to adapt the geometrical compression ratio offer advantages in terms of part load efficiency and maximum power output. In this study a conrod based two-stage VCR system with an eccentric piston pin bearing is investigated in fired engine operation by means of a specially designed measurement technique. For this purpose different sensor technologies were equipped to a VCR conrod and the oil supply system of a prototype crankshaft. The data transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Hammermueller et al [23] found that especially for turbocharged SI engines, the variable geometrical compression ratio is beneficial in terms of part load efficiency and maximum power output. Using a conrod-based two-stage VCR system with an eccentric piston pin bearing, they analyzed the influencing parameters resulting from the fired engine operation, such as dynamic pressure stimulation in the crankshaft oil supply or the acceleration of the internal oil columns.…”
Section: Present State Of the Development Of Vcr And Acc Engines 21 T...mentioning
confidence: 99%
“…Hammermueller et al [23] found that especially for turbocharged SI engines, the variable geometrical compression ratio is beneficial in terms of part load efficiency and maximum power output. Using a conrod-based two-stage VCR system with an eccentric piston pin bearing, they analyzed the influencing parameters resulting from the fired engine operation, such as dynamic pressure stimulation in the crankshaft oil supply or the acceleration of the internal oil columns.…”
Section: Present State Of the Development Of Vcr And Acc Engines 21 T...mentioning
confidence: 99%